2019
DOI: 10.31590/ejosat.658839
|View full text |Cite
|
Sign up to set email alerts
|

Clomazone Aktif Maddesinin Yarı Kurak Koşullarda Geleneksel Pamuk (Gossypium hirsutum L.) Tarlalarında Yabancı Ot Kontrolünde Çıkış Öncesi Herbisitlerle Tank Karışımı

Abstract: Öz Başarılı pamuk üretiminin kritik bileşenlerinden biri, etkili yabani ot yönetimidir. Pamuk (Gossypium hirsutum L.), yabani otlarla yeterince rekabet edemediğinden, özellikle ilk altı haftada, bazı yabani ot türleri pamuk verimini önemli ölçüde azaltmaktadır. Ayrıca yabani otlar pamuk hasadını zorlaştırabilir ve lifini kirletebilir. Türkiye geleneksel pamuk üretiminde (toleranslı ve dayanıklı olmayan çeşitler) özellikle geniş yapraklı yabancı ot kontrolü için tercih edilen temel yöntem, ekim öncesi veya çıkı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Looking at the weed species found in cotton by family, the Poaceae family ranked first with 7 species, followed by the Asteraceae with 6 species, the Euphorbiaceae and the Amaranthaceae family with 5 species (Figure 1). Similar to our study, in studies conducted in cotton growing areas in Türkiye, most of the weed species found in cotton were found to belong to the Poaceae family (Uludağ and Katkat, 1991;Boz et al, 1995;Arslan, 2012;Arslan, 2021;Özaslan and Bükün, 2013;Özkil , 2019;Kaya and Nemli, 2002;Pala and Mennan, 2019;Şahin et al, 2020;Tursun et al, 2004). It was found that most of the species identified during surveys in cotton growing areas in Ethiopia, China, Kenya and Greece in the world belonged to the Poaceae family (Kimunye, 2011;Tena, 2012;WeiHua et al, 2014;Taye, 2019 andIssayev, 2023).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Looking at the weed species found in cotton by family, the Poaceae family ranked first with 7 species, followed by the Asteraceae with 6 species, the Euphorbiaceae and the Amaranthaceae family with 5 species (Figure 1). Similar to our study, in studies conducted in cotton growing areas in Türkiye, most of the weed species found in cotton were found to belong to the Poaceae family (Uludağ and Katkat, 1991;Boz et al, 1995;Arslan, 2012;Arslan, 2021;Özaslan and Bükün, 2013;Özkil , 2019;Kaya and Nemli, 2002;Pala and Mennan, 2019;Şahin et al, 2020;Tursun et al, 2004). It was found that most of the species identified during surveys in cotton growing areas in Ethiopia, China, Kenya and Greece in the world belonged to the Poaceae family (Kimunye, 2011;Tena, 2012;WeiHua et al, 2014;Taye, 2019 andIssayev, 2023).…”
Section: Resultssupporting
confidence: 88%
“…and found that the prevalence rates of these weeds were over 60, 70 and 80%, respectively, in the last twenty years. Pala and Mennan (2019), in their surveys of cotton fields in the Karacadağ Basin, found that the prevalence of S. halepense was 72%, X. strumarium 86% and Physalis spp. 56%, and the results of the study showed that the prevalence of these weed species is increasing in the region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation